Are There Heterogeneous Impacts of Air Pollution on Mental Health? - Hu, Qingqing; Feng, Yanhong; Xu, Mark (Frontiers in Public Health, 2021)
Many studies have shown that air pollution is closely related with mental health. However, the level of impact and the regulatory mechanism of air pollution on different types of mental health are unknown. Employing the panel data of 51 countries from 2010 to 2017, this paper examines the heterogeneous impact and mediating mechanisms of air pollution on mental health based on panel Tobit random effect model, mediating effect model, and bootstrap test. Our findings show that, first, the heterogeneous impact of air pollution on mental health is reflected in different types of mental health. Specifically, air pollution has a significant positive impact on depression; however, the significant impacts of air pollution on happiness and anxiety are closely related to income level. Second, the heterogeneous impact of air pollution on mental health is reflected in different income levels, i.e. the negative impact of air pollution on happiness is only significant in high-income countries; whereas the positive impact of air pollution on depression and anxiety is only significant in low-income countries. Third, the impact of air pollution on mental health is also heterogeneous under different income levels with different levels of education and population density. Fourth, the mediating effect of physical health on different types of mental health is also heterogeneous. To be specific, the effects of air pollution on depression and anxiety are partly mediated by physical health; whereas the effect on happiness is not. These findings contribute to the understanding of air pollution on public health, and have significant implication for social and public health policy makers.